Circulatory responses to simulated gravitational shifts of blood in man induced by exposure of the body below the iliac crests to sub-atmospheric pressure - Brown, E; Goei, J S; Greenfield, A D; Plassaras, G C (The Journal of physiology, 1966)
1. Exposure of the body from iliac crests to feet of a horizontal subject to a pressure 70 mm Hg below atmospheric causes a displacement of about 10 g of blood/kg total body weight from the upper to the lower part of the body. Much of this blood is returned very rapidly at the end of suction.2. During suction, the changes in the circulation resemble those during a foot-down tilt. After suction, the changes resemble to some extent those following the Valsalva manoeuvre.3. The overshoot of forearm blood flow following suction is caused by variations in the activity of adrenergic vasoconstrictor nerves. The receptors for this reflex have not been identified, but their stimulation depends upon a rapid and large return of blood to the central circulation.